2022
DOI: 10.3390/foods11233830
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gelation Properties of Silver Carp Myosin Treated by Combination of High Intensity Ultrasound and NaCl

Abstract: The molecular behavior of myosin in a low-salt environment limited the production of surimi-based products. This study aimed to investigate the effect of the combination of high intensity ultrasound (HIU) and NaCl (0.1, 0.3, 0.5 mol/L) on the physicochemical indexes of myosin. The changes were evaluated by solubility, ultraviolet (UV) spectroscopy, dynamic rheological properties, water holding capacity (WHC), microstructures, etc. For control samples, the gelation properties of myosin strengthened upon NaCl in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It was reported that the addition of myofibril pre-emulsified oil enhanced the gel strength and water retention of shrimp gel [11]. Gao et al [12] found that ultrasonic treatment could significantly enhance the gel properties of silver carp myosin with low NaCl contents. Additionally, the addition of hydrophilic colloids (carrageenan, xanthan gum, konjac gum, etc.)…”
Section: Animal Protein Gelsmentioning
confidence: 99%
“…It was reported that the addition of myofibril pre-emulsified oil enhanced the gel strength and water retention of shrimp gel [11]. Gao et al [12] found that ultrasonic treatment could significantly enhance the gel properties of silver carp myosin with low NaCl contents. Additionally, the addition of hydrophilic colloids (carrageenan, xanthan gum, konjac gum, etc.)…”
Section: Animal Protein Gelsmentioning
confidence: 99%